2014
DOI: 10.1111/ejn.12646
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐like glial cells physiologically regulate olfactory processing through the modification of ORNPN synaptic strength in Drosophila

Abstract: Astrocyte-like glial cells are abundant in the central nervous system of adult Drosophila and exhibit morphology similar to astrocytes of mammals. Previous evidence has shown that astrocyte-like glial cells are strongly associated with synapses in the antennal lobe (AL), the first relay of the olfactory system, where olfactory receptor neurons (ORNs) transmit information into projection neurons (PNs). However, the function of astrocyte-like glia in the AL remains obscure. In this study, using in vivo calcium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…In the olfactory circuit, stimulation of astrocytes using channel rhodopsin 2 (ChR2) inhibited odor-evoked responses of second-order olfactory projection neurons. Astrocyte activation decreased the amplitude and slope of excitatory postsynaptic potentials after antennal nerve stimulation (Liu et al 2014). These data begin to make a case for astrocytes directly reg-…”
Section: Roles For Astrocytes In Neural Circuit Function and Behaviormentioning
confidence: 74%
“…In the olfactory circuit, stimulation of astrocytes using channel rhodopsin 2 (ChR2) inhibited odor-evoked responses of second-order olfactory projection neurons. Astrocyte activation decreased the amplitude and slope of excitatory postsynaptic potentials after antennal nerve stimulation (Liu et al 2014). These data begin to make a case for astrocytes directly reg-…”
Section: Roles For Astrocytes In Neural Circuit Function and Behaviormentioning
confidence: 74%
“…Although they did not examine the underlying anatomy, results of Liu et al (2014) in the olfactory pathway of Drosophila lend support to the notion that astrocytes regulate synaptic signaling in this species: they overexpressed the TrpA1 channel in astrocytes and found that thermogenetic astrocyte activation modulates excitatory post-synaptic potentials in antennallobe projection neurons. The nature of the anatomical relationship between astrocytes and those synapses, however, was not investigated.…”
Section: Spatial Relationships That Support Astrocyte Regulation Of Smentioning
confidence: 99%
“…Whereas sleep homeostasis is beginning to be understood, there is little known about the circadian control of sleep. Therefore, it is of interest that a mutant called wide awake ( wake ) alters the clock regulation of sleep (Liu et al, 2014). WAKE is required within a subset of the PDF neurons (the l-LNv cells) where it interacts with the GABA-A receptor to modulate excitability of these neurons.…”
Section: Studies Of Glial Cell Function In Circadian Behavior and mentioning
confidence: 99%